2021
DOI: 10.1186/s12885-021-07946-x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions of targeted therapy in cancer patients: a retrospective study of hospital medical data in China

Abstract: Background The adverse reactions (ADRs) of targeted therapy were closely associated with treatment response, clinical outcome, quality of life (QoL) of patients with cancer. However, few studies presented the correlation between ADRs of targeted therapy and treatment effects among cancer patients. This study was to explore the characteristics of ADRs with targeted therapy and the prognosis of cancer patients based on the clinical data. Methods A re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…As con rmed by previous studies, patients with comorbidities and performing combined medicine applications normally had more complicated conditions, the interactions of diseases and drugs might lead to worse body function and aggravation of skin ADRs [29]. Our previous retrospective study indicated that the level of education affected the QoL, which was further con rmed in this study [30]. Indeed, poorly educated patients generally lacked the awareness to actively gain information to improve their QoL.…”
Section: Discussionsupporting
confidence: 77%
“…As con rmed by previous studies, patients with comorbidities and performing combined medicine applications normally had more complicated conditions, the interactions of diseases and drugs might lead to worse body function and aggravation of skin ADRs [29]. Our previous retrospective study indicated that the level of education affected the QoL, which was further con rmed in this study [30]. Indeed, poorly educated patients generally lacked the awareness to actively gain information to improve their QoL.…”
Section: Discussionsupporting
confidence: 77%
“…Nonetheless, the risk of AEs is markedly attenuated with targeted therapy administered concomitantly with backbone chemotherapy (FOLFOX, FOLFIRI, CAPEOX, or FOLFOXIRI) for CRC [ 18 , 19 ]. According to a retrospective study, the risk of AEs is substantially elevated with drug combinations and intravenous chemotherapy administration, being the major route of administration of both chemotherapy and targeted therapy agents in mCRC patients [ 6 ]. However, up to now, a choice of effective first-line biologic chemo-treatment with either cetuximab or bevacizumab in patients with RAS wild-type for mCRC is a still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR inhibitors, on the other hand, are only recommended in patients with RAS wild-type left-sided mCRC, as EGFR antibodies only elicit responses in patients with RAS wild-type mCRC, implying that genetic variability is significantly associated with patient outcomes [ 3 ]. Previous studies demonstrated superior efficacy of cetuximab over bevacizumab [ 4 , 5 ]; however, comprehensive comparative analysis on tolerability, especially on serious adverse events (SAEs) in patients receiving cetuximab or bevacizumab is still lacking despite markedly increased the risk of adverse events (AEs) with concomitant administration of chemotherapy such as 5-fluorouracil, leucovorin, irinotecan, or oxaliplatin [ 6 ]. In general, the choice of first-line treatment should be influenced by the tolerability of the medication as well as the patient’s characteristic and efficacy outcomes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many combinations of drugs have been found effective in relevant studies, formulating reasonable drug treatment strategies are still needed to minimize the risk of ADRs in children. In order to minimize the risk of SADRs, physicians should pay particular attention to children who are prescribed two or more drugs and closely monitor drug administration and ( 32 ).…”
Section: Discussionmentioning
confidence: 99%